O Sistema E.R.P. como instrumento de apoio à tomada de decisão aplicado às empresas - Felix, Raul (2014)
This case study shows the trajectory of a company that develops and controls the margin of the fundamentals of Accounting Theory and invests in the implementation of ERP (Enterprise Resource Planning), as a tool to support decision making. The goal is to demonstrate the adverse consequences that may result from the failure of fundamental procedures for the implementation of systems to get the expected result, ie, bring useful and consistent to be used as efficient tools for information governance. Justified this work, considering the number of companies that find it difficult when looking to develop their internal management controls, using ERP systems. The research method based on the theory of Gregory Zoughbi be used. Will examine the role of the Comptroller and factors that may have contributed to the failure of the company, paving the way for new researchers in further studies and research to advance the deepening of the theme. Among the issues to be discussed is the possibility of asserting that the implementation and operation of ERP system, by itself, can be considered as an effective tool in business management ?; Or, in the implementation of the ERP system, the Comptroller has a fundamental role in ensuring the integrity of information and the full operation of methods shared information ?; Or the Comptroller and ERP system can influence the failure of the company?.In this paper, descriptive and deductive method was used